2019
DOI: 10.1103/physrevb.100.174505
|View full text |Cite
|
Sign up to set email alerts
|

Critical field behavior of a multiply connected superconductor in a tilted magnetic field

Abstract: We report magnetotransport measurements of the critical field behavior of thin Al films deposited onto multiply connected substrates. The substrates were fabricated via a standard electrochemical process that produced a triangular array of 66 nm diameter holes having a lattice constant of 100 nm. The critical field transition of the Al films was measured near Tc as a function of field orientation relative to the substrate normal. With the field oriented along the normal (θ = 0), we observe reentrant supercondu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…3(a), the reentrant superconductivity phenomenon occurs, i.e., non-zero resistances below T c0 appear again at low temperatures, which has been reported in a large variety of superconductors. [44][45][46][47][48][49][50]55] We have found that the reentrant superconductivity can be obtained in the curved sample at small θ and low currents or at large θ and high currents, as shown in Figs. 3(a) and 6(a).…”
Section: The ρ(T) At High Currentsmentioning
confidence: 71%
“…3(a), the reentrant superconductivity phenomenon occurs, i.e., non-zero resistances below T c0 appear again at low temperatures, which has been reported in a large variety of superconductors. [44][45][46][47][48][49][50]55] We have found that the reentrant superconductivity can be obtained in the curved sample at small θ and low currents or at large θ and high currents, as shown in Figs. 3(a) and 6(a).…”
Section: The ρ(T) At High Currentsmentioning
confidence: 71%
“…Despite numerous studies on the angular dependence of transport properties in superconductors with random 0D and 1D defects, these are rare for periodic CDs in metallic [37,38] and copper-oxide superconductors [16,26]. Figure 4a presents the angular dependence of our nanopatterned sample at T = 74 K, which is the same reduced temperature t = 0.96 as used for the pristine reference sample.…”
Section: Resultsmentioning
confidence: 99%
“…A second, although smaller, segment of the research effort is focused on novel quantum effects that can arise in BCS superconductors under certain conditions. Examples include non-equilibrium dynamics in Zeeman-limited superconductors [11,12], disorder and correlation effects in thin film systems [13][14][15], phase effects in systems having non-trivial multiply connected geometries [16][17][18], and, of course, quantum entanglement [19,20]. The results reported here fall into the latter category.…”
Section: Introductionmentioning
confidence: 89%